Wissenschaftliche Episteme und Geltung. Von der Konstruktion zum Dialog - P. Goeke (Geographica Helvetica, 2023)
The long triumph of constructivism, particularly visible works such as Kuhn's writing on the structure of scientific revolutions, and many other scientific studies have made one thing clear: Reason alone does not decide on scientific topics, theories, and methods. Instead, very different factors, often considered illegitimate, help determine the course of science. These findings make scientific enlightenment gestures recurrently appear as sheer mockery, undermine the validity claims of scientific statements, open up possibilities for a strong politicisation of science and block any retrograde way out. Those who are nevertheless convinced of the importance of scientific autonomy, who defend a special validity of scientific knowledge and who accept the scientific duty of responsiveness, should acknowledge the decision-making challenges in science and, as the article recommends, engage in theory-theoretical dialogues.